Development of an Aotearoa New Zealand adapted Mediterranean dietary pattern and Kai/food basket for the He Rourou Whai Painga randomised controlled trial - Worthington, Anna; Liu, Eva; Foster, Meika; Wright, Summer Rangimaarie; Lithander, Fiona E.; Wall, Clare; Roy, Rajshri; Parry-Strong, Amber; Krebs, Jeremy; Braakhuis, Andrea (Frontiers in Nutrition, 2024)
Following a Mediterranean diet (MedDiet) is associated with a lower risk of cardiovascular disease.He Rourou Whai Painga is a dietary intervention trial with behaviour change support that seeks to determine whether a MedDiet pattern can provide equivalent benefits in Aotearoa New Zealand 3 (NZ), a country where cardiovascular disease is a leading cause of death. To do this, the MedDiet needs to be adapted in an acceptable way for NZ, with consideration of the Māori (indigenous) population.The MedDiet was defined using existing MedDiet scoring tools and adapted to the NZ context using local guidelines. The resulting NZ MedDiet pattern was used to develop a kai/food basket, including products from industry partners, for participants in He Rourou Whai Painga. Criteria set for the kai/food basket included providing up to 75% of energy requirements and falling within the Australia/NZ Acceptable Macronutrient Distribution Range to reduce risk of chronic disease. Māori researchers on the team provided support to ensure Mātauranga Māori (Māori knowledge and values) was upheld through this process.The NZ MedDiet pattern criteria was similar to the identified MedDiet scoring tools, with differences in recommendations for dairy, red meat, alcohol and olive oil. The resulting kai/food baskets were estimated to provide on average 73.5% of energy requirements for households, with 36% from fat, 8.6% from saturated fat, 17% protein, and 42% carbohydrate. Forty-two industry partners, including 3 Māori businesses, agreed to provide 22 types of food products towards the total.Small, feasible changes to the MedDiet can be made to align with the NZ guidelines and food environment. However, this eating pattern still differs from what the population, particularly Māori, are currently consuming. Continued partnership with Māori and additional behavioural support is important to facilitate adherence to this dietary pattern within He Rourou Whai Painga.